2020
DOI: 10.3389/fgene.2019.01324
|View full text |Cite
|
Sign up to set email alerts
|

USP37 Promotes Lung Cancer Cell Migration by Stabilizing Snail Protein via Deubiquitination

Abstract: Snail is a prominent epithelial-mesenchymal transition (EMT) transcription factor and promotes metastasis. However, Snail protein is unstable and is quickly degraded through ubiquitination-mediated proteasome pathway. Deubiquitinases prevent Snail degradation by regulating the ubiquitination-mediated hydrolysis process. Our studies demonstrate that a deubiquitinating enzyme (DUB) family member, USP37, can deubiquitinate Snail and prevent degradation of Snail. USP37 is co-localized with Snail in the nucleus. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…By in vivo assay, USP37 downregulation also suppressed the tumor growth of MCF-7/ADR cells. The results are consistent with the previous reports that USP37 knockdown significantly inhibited the tumor formation of malignancies, such as lung cancer 18 , kidney cancer 19 , hepatocellular cancer 20 . Inordinate cell cycle progression resulted in tumorigenesis 21 .…”
Section: Discussionsupporting
confidence: 93%
“…By in vivo assay, USP37 downregulation also suppressed the tumor growth of MCF-7/ADR cells. The results are consistent with the previous reports that USP37 knockdown significantly inhibited the tumor formation of malignancies, such as lung cancer 18 , kidney cancer 19 , hepatocellular cancer 20 . Inordinate cell cycle progression resulted in tumorigenesis 21 .…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that expression of these factors is tightly controlled by DUBs. Snail protein can be deubiquitinated and stabilized by USP26, USP11, USP10, USP37 or OTUB1 [55][56][57][58][59]. Slug can be stabilized by USP10 and DUB3 [55,60].…”
Section: Discussionmentioning
confidence: 99%
“…Publicly available ChIP-seq datasets reveal JUN-1 and DAF-16 binding peaks upstream of math-33 (WormBase, release WS274), indicating direct transcriptional control by KGB-1-associated transcription factors. Dysregulation of deubiquitinases has been linked to several human diseases including cancers and neuropathologies 81 , 86 , 87 . Due to its association with KGB-1 and VHP-1, we implicate an additional role for MATH-33.…”
Section: Discussionmentioning
confidence: 99%